The impact of communication satisfaction in the motivation and job satisfaction of employees, in the remote or hybrid work context - Leandro, Beatriz da Costa (2023)
The year 2020 was marked by the beginning of the greatest crisis of the last times – the Covid-19 pandemic. Because of this crisis, organizations have had to adapt their working methods, as they were forced to start working remotely, and leaders and employees have had to adapt to this new reality. This research intends to analyze what were the changes that happened during these times, regarding variables such as employee motivation, job satisfaction, commitment, and performance. The goal of this research is to fill in the gap in the literature, mainly in studies that approach the relationships between adaptive leadership, motivation, satisfaction, commitment, and communication satisfaction, as well as understand the mediating role of communication satisfaction in those relationships. This research will be relevant to understand the impact of an effective communication between leaders and employees, as well as it will help organizations to understand whether it is advantageous to keep implementing remote or hybrid work, from a perspective of their employees’ motivation, job satisfaction, and commitment, according to an adaptive leadership style. For this, an online survey was elaborated and sent to different employees who had to start working remotely after the beginning of the pandemic, where we used several scientifically validated questionnaires and scales, attaining a final sample of 122 participants. The results achieved suggest that there were indeed significant changes in variables like communication satisfaction, adaptive performance, and commitment, from before to after the pandemic. The results also suggest that a leader with adaptive characteristics positively influences the motivation of an employee, their commitment, and their communication satisfaction, as well as it suggests that the perceived communication satisfaction positively influences the employees’ motivation and job satisfaction. On the other hand, the obtained results show that an adaptive leader does not influence the satisfaction that an employee feels towards their job, nor the perceived communication satisfaction influences their commitment. It was also found that communication satisfaction can have a mediating role on the relationships between adaptive leadership and motivation and satisfaction, but not on the relationship between adaptive leadership and commitment.